Specialized Pro-Resolving Lipid Mediators: The Future of Chronic Pain Therapy? (2021)
Chronic pain (CP) is a severe clinical entity with devastating physical and emotional consequences for patients, which can occur in a myriad of diseases. Often, conventional treatment approaches appear to be insufficient for its management. Moreover, considering the adverse effects of traditional analgesic treatments, specialized pro-resolving lipid mediators (SPMs) have emerged as a promising alternative for CP. These include various bioactive molecules such as resolvins, maresins, and protectins, derived from ω-3 polyunsaturated fatty acids (PUFAs); and lipoxins, produced from ω-6 PUFAs. Indeed, SPMs have been demonstrated to play a central role in the regulation and resolution of the inflammation associated with CP. Furthermore, these molecules can modulate neuroinflammation and thus inhibit central and peripheral sensitizations, as well as long-term potentiation, via immunomodulation and regulation of nociceptor activity and neuronal pathways. In this context, preclinical and clinical studies have evidenced that the use of SPMs is beneficial in CP-related disorders, including rheumatic diseases, migraine, neuropathies, and others. This review integrates current preclinical and clinical knowledge on the role of SPMs as a potential therapeutic tool for the management of patients with CP.